Prevalence of keratoconus in persons with Down syndrome: a review - Liv Drolsum; Olav Kristianslund (BMJ Open Ophthalmology, 2021)
Purpose Keratoconus is a vision-threatening condition, and there is a need for knowledge about the occurrence in subgroups of the population. The progression of the disease can be effectively stopped, and vision may be restored, if keratoconus is diagnosed at an early stage. The purpose of this review was to evaluate the literature of the prevalence of keratoconus in persons with Down syndrome.Methods We conducted a literature review of keratoconus prevalence in persons with Down syndrome. A thorough search was performed in Pubmed (Medline), and the quality of evidence was evaluated.Results The literature review identified 20 relevant studies, which reported keratoconus in 0%–71% of persons with Down syndrome. These studies varied greatly in design, patient selection, sample sizes and mean age, and the quality of evidence concerning estimates for the prevalence of keratoconus was generally evaluated as low. Most studies that included adults reported high prevalences of keratoconus–in many studies more than 10-fold the prevalence in the general population. No large screening studies in persons with Down syndrome were identified.Conclusions The present review showed that the prevalence of keratoconus in persons with Down syndrome is higher than in the general population. However, estimates from previous studies vary widely. Screening for keratoconus in this group should be considered.